Investment Gaps after the Crisis - Lewis, Christine (OECD Publishing, 2014)
The downturn in fixed investment among advanced economies from the onset of the global crisis was unusually severe, widespread and long-lasting relative to comparable episodes in the past. As a result, investment gaps are large in many countries, not only in relation to past norms but also relative to projected future steady-state levels, with a gap of 2 percentage points of GDP or more in several countries. A significant proportion of this investment shortfall is attributable to soft demand conditions (the accelerator effect) but financial factors and heightened uncertainty have also played a role. In addition to continued support to demand from macroeconomic policies, the recovery in investment could be boosted by tackling longer-term policy issues that bear on investment decisions indirectly, by reducing financial fragmentation in the euro area and by undertaking growth-friendly structural reforms
Keywords: Economics